2013
DOI: 10.1179/1743278212y.0000000050
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on corrosion behaviour of X70 steel in high pressure CO2/SO2/O2/H2O environments

Abstract: The corrosion study of the pipeline steel is extremely important for the safety of CO 2 pipeline. The present work studied the effect of temperature on the corrosion behaviour of X70 steel in high pressure CO 2 /SO 2 /O 2 /H 2 O mixtures. Weight loss method was utilised to measure the corrosion rate. Environmental scanning electron microscopy and focused ion beam technology were employed to observe the morphology of product scales. X-ray diffraction was used to analyse the composition of product scales. The po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 36 publications
1
33
0
1
Order By: Relevance
“…However, Xiang et al [84] have utilised focused ion beam etching to look into the structure of a spherical FeSO4 corrosion product (shown in Figure 6(d)). Observations from the etching process revealed that small micro-pores existed within the crystalline film, but these were not connected and 27…”
Section: (Figures 6(g) and (H))mentioning
confidence: 99%
See 1 more Smart Citation
“…However, Xiang et al [84] have utilised focused ion beam etching to look into the structure of a spherical FeSO4 corrosion product (shown in Figure 6(d)). Observations from the etching process revealed that small micro-pores existed within the crystalline film, but these were not connected and 27…”
Section: (Figures 6(g) and (H))mentioning
confidence: 99%
“…In general, three typical corrosion morphologies are reported in literature; a thin sulphur-rich cracked film [27,78,82,83] (Figures 6(a), (b) and (c)), columnar/spherical crystals of FeSO3/FeSO4 [4,78,84] (Figures 6(d), (e) and (f)), and globular crystals of FeCO3 [78,81] …”
mentioning
confidence: 99%
“…Apparently, hydrated ferrous sulfate (FeSO 4 ·xH 2 O) are the main composition of product films. In contrast, Hua et al [44] pointed out that hydrated ferrous sulfite (FeSO 3 ·xH 2 O) are the main composition of product films that are exposed to water-saturated CO 2 phase at 35 °C and 8 MPa containing different concentration levels of The reaction mechanisms associated with the formation of FeSO 4 in this work have been pointed out by Xiang et al [8,17] and Choi et al [21]. The possible reaction mechanisms that include anodic and cathodic reactions are as follows:…”
Section: Analysis Of Corrosion Product Morphology and Compositionmentioning
confidence: 76%
“…In the past several years, carbon steel corrosion in supercritical CO 2 with water, oxygen, SO 2 , and other impurities has received increasing attention [6,8,[10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Several studies have focused on corrosion in liquid CO 2 [20,24,25] and the CO 2 capture process [26,27], which are beyond the focus of this paper.…”
mentioning
confidence: 99%
“…[1][2][3] However, most of the existing studies focused on the uniform corrosion behaviour of metals in supercritical CO 2 environments, while in practical CO 2 pipeline transport, localised corrosion, which usually needs a long period to form and develop, is more harmful to the operation safety. The transformation mechanisms of corrosion products under long term condition are also not clear.…”
Section: Introductionmentioning
confidence: 99%